IPhone the missing manual - Pogue, David 1963- (O'Reilly Media, Inc., 2018)
IOS 11 for the iPhone includes a host of exciting new features, including a revamped Control Center and all-new powers for some of your favorite apps--Siri, AirPlay 2, Maps, Photos, and Maps. You can even send payment via iMessages and type with one hand! And the best way to learn all of these features is with iPhone: The Missing Manual--a funny, gorgeously illustrated guide to the tips, shortcuts, and workarounds that will turn you, too, into an iPhone master. This easy-to-use book will help you accomplish everything from web browsing to watching videos so you can get the most out of your iPhone. Written by Missing Manual series creator and former New York Times columnist David Pogue, this updated guide shows you everything you need to know about the new features and user interface of iOS 11 for the iPhone.
Includes index. - Vendor-supplied metadata
Keywords: iPhone (Smartphone) -- Handbooks, manuals, etc; Smartphones -- Handbooks, manuals, etc; Pocket computers -- Handbooks, manuals, etc; Cell phones -- Handbooks, manuals, etc; Mobile computing -- Handbooks, manuals, etc; iPhone (Téléphone intelligent); Guides, manuels, etc; Téléphones intelligents; Guides, manuels, etc; Ordinateurs de poche; Guides, manuels, etc; Informatique mobile; Guides, manuels, etc; Téléphones cellulaires; Guides, manuels, etc; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference; Pocket computers; Cell phones; iPhone (Smartphone); Mobile computing; Smartphones; handbooks; Handbooks and manuals; Guides et manuels; Handbook